Evaluating Serum Troponin as a Mortality Predictor in COVID-19: Two Center Prospective Study - Jawad, Muhannd M.; Al-Shirifi, Abbas N. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Severe Acute Respiratory Syndrome Corona Virus 2 induced by a combination of the spike protein of the virus and an angiotensin-converting enzyme 2, which is strongly expressed in the heart and lungs, causing acute myocardial injury with increase serum Troponin level. The identification of a significant cardiac involvement might activate the doctor in cardiology department for follow-up during hospitalization or after COVID-19 recovery.Objectives: evaluating serum troponin as a mortality predictor in COVID-19: two center prospective study.Methods:  A prospective observational study was carried out in Al Yarmouk Teaching Hospital and Dar Al-Salam Hospital, Al-Karkh side of Baghdad-Iraq from 1st of January 2021 to 30th of June 2021 and involved (85) patients confirmed to have COVID-19 by RT-PCR, then screened for cardiac-specific biomarkers as reflected by elevated serum troponin level. Microsoft Excel 2010 and Statistical package for social sciences version 23 were used for data entry. Chi square and t-test was used was used to compare proportions, analyzing data and show any significant difference of the mean age.Results: In this study, 24 (28.2%) patients were with high serum troponin level and the majority 61 (71.8%) were with normal serum troponin level. The highest proportion of high serum troponin level was among smokers and ex-smokers [55.6% (5), and 66.7% (2) respectively. 12 (46.2%) of patients with diabetes were with high serum troponin level. 62.5% (15) of hypertensive patients were significantly with high troponin level (P= 0.018). There was a strong   association between COVID-19 severity and serum troponin level whereas in patients with critical COVID-19 60.9% (14) were within high serum troponin level. There was a significant difference between the outcome of COVID-19 patients and serum troponin level, where the higher serum troponin was in 14 (60.9%) from patients who ended up with death.Conclusion: The study showed a significant relationship between high serum troponin levels and mortality in critical COVID-19 patients. High serum troponin level was significantly associated with diabetes mellitus, hypertension, ischemic heart disease, and smoking. There was no significant association between high serum troponin level and age, sex, asthma, and malignancy.